Benefits of Implicit Regulation of Instructed Fear: Evidence From Neuroimaging and Functional Connectivity - Zhang, Yicheng; Chen, Shengdong; Deng, Zhongyan; Yang, Jiemin; Yuan, Jiajin (Frontiers in Neuroscience, 2020)
Instructed fear, which denotes fearful emotions learned from others’ verbal instructions, is an important form of fear acquisition in humans. Maladaptive instructed fear produces detrimental effects on health, but little is known about performing an efficient regulation of instructed fear and its underlying neural substrates. To address this question, 26 subjects performed an instructed fear task where emotional experiences and functional neuroimages were recorded during watching, explicit regulation (calmness imagination), and implicit regulation (calmness priming) conditions. Results indicated that implicit regulation decreased activity in the left amygdala and left insula for instructed fear; however, these effects were absent in explicit regulation. The implementation of implicit regulation did not increase activity in the frontoparietal control regions, while explicit regulation increased dorsolateral prefrontal cortex activity. Furthermore, implicit regulation increased functional connectivity between the right amygdala and right fusiform gyrus, and decreased functional connectivity between the right medial temporal gyrus and left inferior frontal gyrus, which are key nodes of memory retrieval and cognitive control networks, respectively. These findings suggest a favourable effect of implicit regulation on instructed fear, which is subserved by less involvement of control-related brain mechanisms.